2019
DOI: 10.1515/cclm-2019-0088
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of a fully automated multiplex celiac disease antibody panel for serum and plasma

Abstract: Background An automated multiplex platform using capillary blood can promote greater throughput and more comprehensive studies in celiac disease (CD). Diagnostic accuracy should be improved using likelihood ratios for the post-test probability of ruling-in disease. Methods The Ig_plex™ Celiac Disease Panel on the sqidlite™ automated platform measured IgA and IgG antibodies to tTG and DGP in n = 224 CD serum or plasma samples. Diagnostic accuracy metrics were applied to the combined multiplex test results for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…This study also demonstrated equivalent SARS-CoV-2 IgG assay results using plasma collected by fingerstick or by venipuncture. Fingerstick plasma has been used to detect IgG for the confirmation of celiac disease diagnosis [19] and to detect both IgG and IgM after suspected measles or Rubella infection [7,20]. Collection of fingerstick plasma in Microtainer tubes is quick and easy and does not require a trained phlebotomist, making it a feasible alternative to venipuncture for use in SARS-CoV-2 curbside testing or drive-through testing sites.…”
Section: Discussionmentioning
confidence: 99%
“…This study also demonstrated equivalent SARS-CoV-2 IgG assay results using plasma collected by fingerstick or by venipuncture. Fingerstick plasma has been used to detect IgG for the confirmation of celiac disease diagnosis [19] and to detect both IgG and IgM after suspected measles or Rubella infection [7,20]. Collection of fingerstick plasma in Microtainer tubes is quick and easy and does not require a trained phlebotomist, making it a feasible alternative to venipuncture for use in SARS-CoV-2 curbside testing or drive-through testing sites.…”
Section: Discussionmentioning
confidence: 99%
“…This is important for patients who initially test negative for the IgA tTG and IgA antibodies used for screening but have positive DGP antibodies. The accuracy of venous to capillary plasma samples was proven with 100% agreement analysis for results using the Ig_plex 9…”
Section: Diagnosismentioning
confidence: 99%
“…The accuracy of venous to capillary plasma samples was proven with 100% agreement analysis for results using the Ig_plex. 9 Gluten challenge Patients who do not have a confi rmed celiac disease diagnosis and who are restricting or avoiding gluten in their diet can undergo a gluten challenge. This test lets serum antibody levels rise to a detectable range before screening.…”
Section: Key Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…The accuracy of serologic testing is of tremendous importance, both in the biopsy and no-biopsy approach. Even though the sensitivity and specificity of TGA in the detection of CD is considered very high, it has been demonstrated in various studies that the diagnostic performance may vary depending on the different assays used (9)(10)(11)(12)(13). In this study, we aimed to investigate the real-life performance of a CD serology automated multiplex analyzer (Bioplex 2200, Bio-Rad Laboratories, CA), which is used as the CD serology test at Clalit Health Services, Israel's largest Health Maintenance Organization, and to explore the correlation between TGA levels and intestinal biopsies in children.…”
Section: What Is Newmentioning
confidence: 99%